Sekolah Pancasila: An educational empowerment effort for the Suku Anak Dalam in Sekaladi, Jambi - Simaremare, Tohap Pandapotan; Aulia, Nurul Quraini; Nst, Indra Budiman; Yulias, Putri Oktaviani; As Shalikhah, Sinta Wahidha; Gustiani, Eva; Widodo, Teguh (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
The Suku Anak Dalam (SAD) community in Sekaladi Village, Jambi, experiences inequality in access to education, a fundamental right of every citizen. This disparity has caused delays in their educational development, affecting their understanding of national values and human rights, prompting the Village Innovation Program team from the University of Jambi to implement an educational program called Sekolah Pancasila. This research aims to enhance SAD children's understanding of the values of Pancasila and the concept of Indonesia. This research used qualitative methods with an interactive and case study approach. The research location is in Jambi Province. The results show that the implementation of Pancasila School includes various activities such as literacy and numeracy, community service, civil administration services, and the dissemination of human rights reinforcement through the legal system. Implementing the Pancasila School program has effectively addressed educational disparities within the SAD community. This initiative aims to familiarise SAD children with Pancasila and Indonesian identity while enhancing their critical thinking and participatory skills as empowered citizens.